2018
DOI: 10.1158/1940-6207.capr-17-0368
|View full text |Cite
|
Sign up to set email alerts
|

PAM50 and Risk of Recurrence Scores for Interval Breast Cancers

Abstract: Breast cancers detected after a negative breast screening examination and prior to the next screening are referred to as interval cancers. These cancers generally have poor clinical characteristics compared to screen-detected cancers, but associations between interval cancer and genomic cancer characteristics are not well understood. Mammographically-screened women diagnosed with primary invasive breast cancer from 1993-2013 (n=370) were identified by linking the Carolina Breast Cancer Study and the Carolina M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…[25][26][27][28][29] Our study corroborates previous research showing that IBC tumors are larger and more likely to be advanced, with more lymph node involvement and a higher proportions of lobular histologic characteristics, than breast cancers detected by screening. [5][6][7]11 However, previous studies did not compare IBCs by screening interval. The unique findings from our study are that IBCs that emerge within 1 year after negative mammogram results might have distinct tumor characteristics that identify them as at a particularly high risk for metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27][28][29] Our study corroborates previous research showing that IBC tumors are larger and more likely to be advanced, with more lymph node involvement and a higher proportions of lobular histologic characteristics, than breast cancers detected by screening. [5][6][7]11 However, previous studies did not compare IBCs by screening interval. The unique findings from our study are that IBCs that emerge within 1 year after negative mammogram results might have distinct tumor characteristics that identify them as at a particularly high risk for metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Also, the combination of germline genomic testing with mammography may help distinguish indolent breast cancers from aggressive breast cancers detected by screening. 7 This study adds to a growing body of literature [46][47][48][49] that argues for the development of novel approaches to detect life-threatening cancers currently missed by mammographic screening.…”
Section: Jama Network Open | Oncologymentioning
confidence: 96%
See 1 more Smart Citation
“…That is not surprising given the ability of the PAM50 classification to capture intrinsic biological features and to predict clinical outcomes [10,11]. Others have also reported that interval cancers are associated with both more aggressive non-luminal molecular subtypes and with the PAM50 risk of recurrence score, independently of mammographic density [12]. Because the PAM50 subtypes are mainly a marker for tumour growth rate, it comes easy that tumours that grow within two screening intervals (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Gene expression profiling (GEP) is a powerful tool for discovery and can provide clinically actionable information in many subtypes of malignancies. 15,17,[20][21][22][23][24] Comprehensive classification of acute leukemia using single-platform short-read RNA sequencing is established in research settings, allowing determination of leukemia lineage, genomic subtypes, small mutations, and aneuploidy. 18,25 The base-pair accuracy of short-read sequencing by synthesis makes it the reference standard in cancer research and clinical care in high-income countries.…”
Section: Introductionmentioning
confidence: 99%